Exogenous GR24 Alleviates Cadmium Toxicity by Reducing Cadmium Uptake in Switchgrass (Panicum virgatum) Seedlings - Tai, Zhenglan (Int J Environ Res Public Health, 2017)
Strigolactones (SLs) are classified into plant hormones, playing a key role as a mediator of plant growth in response to several abiotic stresses, including drought and salinity. However, the role of SLs in cadmium (Cd)-induced stress to plants is still unknown. The physiological responses of switchgrass (Panicum virgatum) stressed in 10 μmol L(−1) Cd to exogenous synthetic SLs analog, GR24 were studied in hydroponics. The Cd stress significantly caused the adverse effects on plant growth and root morphology, inhibited photosynthesis, but boosted lipid peroxidation of Switchgrass seedlings. After treatment of 1 μmol L(−1) GR24, the above adverse effects caused by Cd stress were significantly alleviated, mainly reflects in improvement of shoot biomass, relative water content, root development, chlorophyll contents, activities of typical antioxidant enzymes, nutrient uptake. The reason for exogenous GR24 alleviating cadmium toxicity might be owing to that exogenous GR24 promoted the content of endogenous SLs, increased some essential element Fe (iron), Zn (zinc), Mn (manganese) and Cu (copper) uptake and reduced cadmium uptake, accumulation and partition in shoot of switchgrass seedlings.